2005
DOI: 10.1111/j.1600-0579.2004.00351.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of augmented visual feedback from a virtual reality simulation system on manual dexterity training

Abstract: Little research has been published about the impact of simulation technology on the learning process of novel motor skills. Especially the role of augmented feedback (FB) on the quality of performance and the transfer of the acquired behaviour to a no-augmented FB condition require further investigation. Therefore, novice dental students were randomly assigned to one of three groups and given the task of drilling a geometrical class 1 cavity. The FB group trained under augmented visual FB conditions, provided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
3
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 27 publications
4
77
3
5
Order By: Relevance
“…As in a previous study (7), the novice users in this study showed a significant reduction in task completion time (T) after the training sessions. Remarkably, their learning curves for the time score showed that they achieved a drastic time reduction with only a few training sessions.…”
Section: Discussionmentioning
confidence: 53%
“…As in a previous study (7), the novice users in this study showed a significant reduction in task completion time (T) after the training sessions. Remarkably, their learning curves for the time score showed that they achieved a drastic time reduction with only a few training sessions.…”
Section: Discussionmentioning
confidence: 53%
“…This result was in agreement with our previous findings. Wierinck et al 6,7 found that floor smoothness' performance was enhanced by a fluent preparation technique and a reduced preparation time, a typical control group's strategy. More importantly, reducing the relative frequency of feedback during acquisition produced no differential effects on retention testing.…”
Section: Discussionmentioning
confidence: 97%
“…The faster dexterity build-up may have a beneficial influence on the attitude of the dentist towards assimilation of new skills. Wierinck et al 6 showed that manual dexterity training on such a simulator resulted in enhanced performance during acquisition. When feedback was withdrawn, however, performance deteriorated, indicative for feedback dependency.…”
Section: Introductionmentioning
confidence: 98%
“…Simulation will not preclude the need for supervision and training in the clinic, but the uptake of PBL and simulated navigation surgery such as this and its adoption as part of a surgical training curriculum should increase confidence in the surgical profession and is considered to minimize the leap between laboratory and clinic (27,30,37).…”
Section: Limitations Of the Training And Evaluation Techniquementioning
confidence: 98%